High‐Throughput Magnetic Actuation Platform for Evaluating the Effect of Mechanical Force on 3D Tumor Microenvironment. (23rd September 2020) - Enríquez, Ángel; Libring, Sarah; Field, Tyler C.; Jimenez, Julian; Lee, Taeksang; Park, Hyunsu; Satoski, Douglas; Wendt, Michael K.; Calve, Sarah; Tepole, Adrian Buganza; Solorio, Luis; Lee, Hyowon
Abstract: Accurately replicating and analyzing cellular responses to mechanical cues is vital for exploring metastatic disease progression. However, many of the existing in vitro platforms for applying mechanical stimulation seed cells on synthetic substrates. To better recapitulate physiological conditions, a novel actuating platform is developed with the ability to apply tensile strain on cells at various amplitudes and frequencies in a high‐throughput multi‐well culture plate using a physiologically relevant substrate. Suspending fibrillar fibronectin across the body of the magnetic actuator provides a matrix representative of early metastasis for 3D cell culture that is not reliant on a synthetic substrate. This platform enables the culturing and analysis of various cell types in an environment that mimics the dynamic stretching of lung tissue during normal respiration. Metabolic activity, YAP activation, and morphology of breast cancer cells are analyzed within one week of cyclic stretching or static culture. Further, matrix degradation is significantly reduced in breast cancer cell lines with metastatic potential after actuation. These new findings demonstrate a clear suppressive cellular response due to cyclic stretching that has implications for a mechanical role in the dormancy and reactivation of disseminated breast cancer cells to macrometastases. Abstract : A novel magnetically actuating platform is developed that can cyclically stretch 3D cell cultures using suspended fibronectin that mimics the strain amplitude and frequency of the lungs. The findings suggest a suppressive cellular response due to the cyclic stretching, which has implications for a mechanical role in the dormancy and the reactivation of disseminated breast cancer cells in the lungs.